2019
DOI: 10.3892/etm.2019.8293
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑665 promotes the proliferation of ovarian cancer cells by targeting SRCIN1

Abstract: Recent studies have discovered several microRNAs (miRNAs/miRs) as biomarkers for the prediction of ovarian cancer by detecting miRNA profiles in serum samples from healthy volunteers and patients with ovarian cancer. However, whether and how these miRNAs are involved in tumorigenesis is not known. In the present study, the expression of miR-665, a recently discovered biomarker for ovarian cancer, was upregulated in tumor tissues from patients with ovarian cancer compared with normal tissues. Inhibition of miR-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…In ovarian cancer, sustained activation of MAPK/ERK signaling is associated with strong cell proliferation and metastatic potential (73). The western blotting results showed that inhibition of miR-665 increased SRCIN1, at both the mRNA and protein level, and inactivated MAPK/ERK pathway in ovarian cancer (74). Similar findings were reported in the case of miR-150.…”
Section: Mirna-mediated Src Oncogenic Signaling In Selected Cancer Typessupporting
confidence: 72%
“…In ovarian cancer, sustained activation of MAPK/ERK signaling is associated with strong cell proliferation and metastatic potential (73). The western blotting results showed that inhibition of miR-665 increased SRCIN1, at both the mRNA and protein level, and inactivated MAPK/ERK pathway in ovarian cancer (74). Similar findings were reported in the case of miR-150.…”
Section: Mirna-mediated Src Oncogenic Signaling In Selected Cancer Typessupporting
confidence: 72%
“…A plethora of studies have found that miRNAs are involved in multiple steps of tumor diseases, including growth, migration, invasion, metabolism and metastasis [ 25 , 26 ]. Currently, only a few studies have found that miR-665 play an important role in some cancers [ 18 , 21 ]. A previous study reveals that miR-665 expression is correlated with breast cancer survival and miR-665 expression predicts poor and promotes tumor metastasis by targeting NR4A3 [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have found that miRNAs are involved in the oncogenesis, development and transformation of LUSC, such as miR-182-5p, miR-198-5p, miR-223-3p, miR-372-3p [ 14 17 ]. Previous studies have shown that miR-665 is clinically significant and regulates oncogenesis and development in breast cancer, ovarian cancer, liver cancer, gastric cancer, pancreatic cancer, retinoblastoma and lymphoblastic leukemia [ 18 21 ]. However, the clinical significance, precise molecular mechanisms and biological functions of miR-665 in LUSC remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…During our study of tumor inhibition by circ-000881, miR-665 greatly aroused our interest because of its potential binding site with circ-000881, which was revealed by bioinformatics analysis. Many studies have demonstrated miR-665 to be abnormally expressed in tumors such as ovarian cancer (26), gastric adenocarcinoma (27) and hepatocellular carcinoma (28). Liu et al also found that miR-665 expression was upregulated in small cell lung cancer tissues (29).…”
Section: Discussionmentioning
confidence: 99%